A Retrospective Study of Diaphragmatic Breathing Training Combined with Discharge Care Bundles in Patients with Chronic Obstructive Pulmonary Disease. (14th September 2022) - Yu, Shuhui; Lu, Chen; Qin, Lingling
Abstract : Objective . Both physical exercise and discharge care bundles can improve patient outcomes and reduce hospitalization rates among subjects with chronic obstructive pulmonary disease (COPD). The retrospective analysis aims to determine the advantages of care bundles combined with diaphragmatic breathing training (DBT) in COPD patients after discharge. Methods . Of the 110 COPD patients, 55 patients received DBT alone (DBT group) and 55 participants received the combined intervention (care bundle + DBT group). Three months after discharge, we assessed the outcomes of patients using Bristol COPD Knowledge Questionnaire (BCKQ), Hospital Anxiety and Depression Scale (HADS), COPD Assessment Test (CAT), and St. George's Respiratory Questionnaire (SGRQ). Meanwhile, COPD-related hospital readmissions were also recorded. Results . The BCKQ score for assessing the disease knowledge level was increased in patients at 3 months after the combined interventions as compared to the baseline values, which was higher in the care bundle + DBT group than the DBT group at 3 months. Moreover, improvements in negative emotion and clinical symptoms from baseline to 3-month follow-up were seen in both the two groups. Besides, the care bundle + DBT group showed the mitigation of depression and anxiety and the alleviation of clinical symptoms in comparison with the DBT group at 3 months. Participants who received combined interventions had lower SGRQ scores than those who received DBT alone. The time to first COPD-related readmission was shorter for patients in the care bundle + DBT group compared with the DBT group. Conclusions . DBT combined with discharge care bundles for COPD patients resulted in improvements in disease-specific knowledge, negative emotions, and clinical symptoms with better HRQOL and lower readmission rate.